2020
DOI: 10.1159/000502543
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Paradoxical Vocal Fold Motion and Dysphonia in Adolescents

Abstract: Objective: Associations between dysphonia and paradoxical vocal fold motion (PVFM) have been previously reported in adults, but it is unclear whether similar associations exist for adolescents. The goals of this study were to identify the prevalence and severity of voice disorders in adolescent patients with PVFM, identify differences between those with and without clinician-identified dysphonia, and investigate what factors were associated with voice handicap in this population. Methods: A retrospective revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…A total of 1559 references were identified through database searching and 11 additional through reference reviews. After removing duplicates and identifying records from other sources (reference lists of reviews), the titles and abstracts of 1076 studies were screened for relevance, and 31 studies were selected for full‐text review for eligibility, resulting in the inclusion of eight cohort studies: one retrospective chart review, one prospective, and six observational cohort studies 22–29 . No randomized controlled trials (RCTs) were identified.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 1559 references were identified through database searching and 11 additional through reference reviews. After removing duplicates and identifying records from other sources (reference lists of reviews), the titles and abstracts of 1076 studies were screened for relevance, and 31 studies were selected for full‐text review for eligibility, resulting in the inclusion of eight cohort studies: one retrospective chart review, one prospective, and six observational cohort studies 22–29 . No randomized controlled trials (RCTs) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…In two studies, one showed probably the high risk of bias for all domains except detection (probably low risk) 23 ; the other showed probably the low risk of bias for all domains except participant selection and attrition/exclusion (probably high risk). 26 Due to the descriptive nature, small patient numbers, limited recruitment strategies, and reliance on retrospective data with or without a follow-up, all studies had a high risk of bias.…”
Section: Risk Of Biasmentioning
confidence: 96%
See 3 more Smart Citations